2004
DOI: 10.1136/bmj.38097.590810.7c
|View full text |Cite
|
Sign up to set email alerts
|

Rates of caesarean section and instrumental vaginal delivery in nulliparous women after low concentration epidural infusions or opioid analgesia: systematic review

Abstract: Objective To compare the effects of low concentration epidural infusions of bupivacaine with parenteral opioid analgesia on rates of caesarean section and instrumental vaginal delivery in nulliparous women. Data sources Medline, Embase, the Cochrane controlled trials register, and handsearching of the International Journal of Obstetric Anesthesia. Study selection Randomised controlled trials comparing low concentration epidural infusions with parenteral opioids. Data synthesis Seven trials fulfilled the inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
3
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(72 citation statements)
references
References 37 publications
6
60
3
3
Order By: Relevance
“…In this study, the women in the EDA group had a higher VAS score for overall childbirth experience, suggesting that they were more satisfied with their experience than women who did not use EDA. This finding has been supported by other studies, suggesting that EDA is the gold standard resulting in adequate pain relief and increased patient satisfaction [24] [31] [33]. Effective pain management correlates strongly and positively with increased patient satisfaction [50] [51] [52].…”
Section: Discussionsupporting
confidence: 68%
“…In this study, the women in the EDA group had a higher VAS score for overall childbirth experience, suggesting that they were more satisfied with their experience than women who did not use EDA. This finding has been supported by other studies, suggesting that EDA is the gold standard resulting in adequate pain relief and increased patient satisfaction [24] [31] [33]. Effective pain management correlates strongly and positively with increased patient satisfaction [50] [51] [52].…”
Section: Discussionsupporting
confidence: 68%
“…Results of randomised controlled trials (RCTs) and systematic reviews published between 2002 and 2004 did not demonstrate any difference in the rate of caesarean deliveries between women who had received EA and women who only received intravenous analgesia. 1,[3][4][5][6] A Cochrane review, published, in 2005, showed that EA was associated with an increased risk of instrumental vaginal birth (pooled risk ratio [RR] 1.38, 95% CI 1.24-1.53) compared with deliveries with nonepidural analgesia or no analgesia. 2 A landmark study by Wong et al, 7 published in 2005, provided evidence that early epidurals in comparison with late epidurals do not cause an increased rate of caesarean deliveries and instrumental vaginal deliveries in nulliparous women with spontaneous labour.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been shown to result in a lower risk of IVD; 5 however, the rate of IVD is still higher than that in women with no epidural. 6 Reducing the rate of IVD and increasing the spontaneous vaginal birth (SVB) rate would reduce short-and long-term morbidity for women by reducing the risk of perineal trauma and the effects of surgical repair. The incidence of perineal pain, dyspareunia and incontinence following IVD could also be reduced.…”
Section: Scientific Backgroundmentioning
confidence: 99%